KW2449 ameliorates collagen-induced arthritis by inhibiting RIPK1-dependent necroptosis - Wang, Qiong; Ye, Qinbin; Xi, Xiaoyu; Cao, Xiaoxue; Wang, Xing; Zhang, Mengxiao; Xu, Yuan; Deng, Tingting; Deng, Xiaobing; Zhang, Guoqiang; Xiao, Cheng (Frontiers in Immunology, 2023)
Objective. Necroptosis has recently been found to be associated with the pathogenesis of many autoimmune diseases, including rheumatoid arthritis (RA). This study was undertaken to explore the role of RIPK1-dependent necroptosis in the pathogenesis of RA and the potential new treatment options. Methods. The plasma levels of receptor-interacting protein kinase 1 (RIPK1) and mixed lineage kinase domain-like pseudokinase (MLKL) in 23 controls and 42 RA patients were detected by ELISA. Collagen-induced arthritis (CIA) rats were treated with KW2449 by gavage for 28 days. Arthritis index score, H&E staining, and Micro-CT analysis were used to evaluate the joint inflammation. The levels of RIPK1-dependent necroptosis related proteins and inflammatory cytokines were detected by qRT-PCR, ELISA and Western blot, and the cell death morphology was detected by flow cytometry analysis and high-content imaging analysis. Results. The plasma levels of RIPK1 and MLKL in RA patients were higher than those in healthy people, and were positively correlated with the severity of RA. KW2449 could reduce joint swelling, joint bone destruction, tissue damage, and the plasma levels of inflammatory cytokines in CIA rats. Lipopolysaccharide combined with zVAD (LZ) could induce necroptosis in RAW 264.7 cells, which could be reduced by KW2449. RIPK1-dependent necroptosis related proteins and inflammatory factors increased after LZ induction and decreased after KW2449 treatment or knockdown of RIPK1. Conclusion. These findings suggest that the overexpression of RIPK1 is positively correlated with the severity of RA. KW2449, as a small molecule inhibitor targeting RIPK1, has the potential to be a therapeutic strategy for RA treatment by inhibiting RIPK1-dependent necroptosis.